Behind Enemy Lines: Immunomodulatory Armamentarium of the Schistosome Parasite - Angeles, Jose Ma. M.; Mercado, Van Jerwin P.; Rivera, Pilarita T. (Frontiers in Immunology, 2020)
The deeply rooted, intricate relationship between the Schistosoma parasite and the human host has enabled the parasite to successfully survive within the host and surreptitiously evade the host’s immune attacks. The parasite has developed a variety of strategies in its immunomodulatory armamentarium to promote infection without getting harmed or killed in the battlefield of immune responses. These include the production of immunomodulatory molecules, alteration of membranes and the promotion of granuloma formation. Schistosomiasis thus serves as a paradigm for understanding the Th2 immune responses seen in various helminthiases. This review therefore aims to summarize the immunomodulatory mechanisms of the schistosome parasites to survive inside the host. Understanding these immunomodulatory strategies not only provides information on parasite-host interactions, but also forms the basis in the development of novel drugs and vaccines against the schistosome infection, as well as various types of autoimmune and inflammatory conditions.